The effects of maternal serum lipid on maternal blood pressure and fetal birth weight: a prospective cohort study - Nusee, Zalina; Hoe, Kah Seong; Ismail, Hamizah; Abdullah, Suhaiza; Htike, Myat Phyu; Abdullah, Nor Zamzila; Mohd Rus, Razman (Omiconline, 2015)
Objective: This study was conducted to assess the social-demographic characteristic and the effect of maternal fasting serum lipids between trimesters and its effect on maternal blood pressure and fetal birth weight. Materials and methods: A prospective cohort study was designed for recruiting pregnant women who were in their 1st trimester at a primary maternal child health center (KKIA). The study involved taking fasting serum lipids (FSL), blood pressure (BP) measuring and urine albumin in every trimester. Results: Fasting serum triglyceride (TG), low density lipoprotein (LDL), high density lipoprotein (HDL) and total cholesterol (TC) were significantly (p<0.05) increased as the gestational age increased. There were no significant changes in blood pressure and urine albumin throughout the pregnancy. Serum lipid did not statistically influence the birth weight (P=0.922). Meanwhile serum triglyceride level was double (4.5 mmol/L) in one patient who developed eclampsia. Conclusion: Serum lipid increase in parallel to increase in gestational age however it does not influenced the maternal blood pressure and birth weight. Further study with larger sample size is required to confirm the factors associated with PE.